The UNIDROIT principles in practice : caselaw and bibliography on the UNIDROIT principles of international commercial contracts - Bonell, Michael Joachim (Transnational Publishers, 2006)
Since fall 2006: a new, revised edition of Unidroit Principles in Practice, featuring approximately 120-130 cases. The UNIDROIT Principles of International Commercial Contacts, published in 1994, were an entirely new approach to international contract law. Prepared by a group of eminent experts from around the world as a "restatement" of international commercial contract law, the Principles are not a binding instrument but are referred to in many legal matters. They are widely recognized now as a balanced set of rules designed for use throughout the world irrespective of the legal traditions a